1983
DOI: 10.1002/jmv.1890120105
|View full text |Cite
|
Sign up to set email alerts
|

Episomal DNA of a BK virus variant in a human insulinoma

Abstract: BK virus (BKV) DNA was detected by blot hybridization in a human adenoma of pancreatic islets from patient I.R. BKV DNA was free, and no evidence was found of viral sequences integrated into cellular DNA. Virus was rescued by transfection of human embryonic fibroblasts with tumor DNA. The DNA from rescued virus (BKV-IR) was different from wild-type BKV DNA by restriction endonuclease mapping. The genome of BKV-IR is 235 base pairs (bp) shorter than the genome of wild-type BKV. This alteration originates from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…This restriction pattern is similar to that of BKV-IR (Fig. 2), a BKV variant rescued from a human tumour of pancreatic islets (Caputo et al, 1983;Pagnani et al, 1986) and is compatible with an insertion into the regulatory region of the viral genome, which is in HindlII fragment C, as well as with a deletion around map unit 0.54 where a BgllI site and the HindlII site between fragments B and D are located.…”
supporting
confidence: 68%
“…This restriction pattern is similar to that of BKV-IR (Fig. 2), a BKV variant rescued from a human tumour of pancreatic islets (Caputo et al, 1983;Pagnani et al, 1986) and is compatible with an insertion into the regulatory region of the viral genome, which is in HindlII fragment C, as well as with a deletion around map unit 0.54 where a BgllI site and the HindlII site between fragments B and D are located.…”
supporting
confidence: 68%
“…Small tag cooperates with large Tag in transformation by reducing serum dependence of transformed cells (Bouck et al, 1978;Sleigh et al, 1978;Martin et al, 1979;Frisque et al, 1980). Indeed, a low efficiency of stable transformation and a reduced incidence of tumors with a longer latency period was observed with BKV-IR (Pagnani et al, 1986), a BKV strain bearing a deletion of 253 bp which removes sequences coding for the carboxyl-terminus of small tag (Caputo et al, 1983). Moreover, BKV small tag binds the catalytic (36-kDa) and regulatory (63-kDa) subunits of protein phosphatase 2A (PP2A) (Rundell et al, 1981), inactivating their function.…”
Section: Role Of Bkv Tumor Antigens In Transformation and Oncogenicitymentioning
confidence: 99%
“…Indeed, a lower efficiency of stable transformation and a reduced tumor incidence associated with a longer latency were described as properties of a naturally occurring BKV variant, BKV-IR, lacking the carboxy-terminus of the t-ag. 12,13 The continuous expression of a functional T-ag, detectable in all BKV-transformed cells, is necessary for the maintenance of transformation. 14 Likewise, studies on the highly homologous SV40 virus have demonstrated that T-ag expression is necessary for the maintenance of transformation [15][16][17][18] and its inhibition by antisense RNA in SV40-positive human mesothelioma cells restores p53 function and induces cell growth arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%